2007
DOI: 10.1074/jbc.m608800200
|View full text |Cite
|
Sign up to set email alerts
|

A Putative Src Homology 3 Domain Binding Motif but Not the C-terminal Dystrophin WW Domain Binding Motif Is Required for Dystroglycan Function in Cellular Polarity in Drosophila

Abstract: The conserved dystroglycan-dystrophin (Dg⅐Dys) complex connects the extracellular matrix to the cytoskeleton. In humans as well as Drosophila, perturbation of this complex results in muscular dystrophies and brain malformations and in some cases cellular polarity defects. However, the regulation of the Dg⅐Dys complex is poorly understood in any cell type. We now find that in loss-of-function and overexpression studies more than half (34 residues) of the Dg proline-rich conserved C-terminal regions can be trunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 50 publications
3
29
0
2
Order By: Relevance
“…One copy of the mRpL34 transgene rescues this phenotype completely (Figure 3D). This result was surprising since it has been reported that expression of a Dg transgene also rescues the Dg 248 polarity phenotype (Yatsenko et al., 2007). We therefore reproduced this experiment and confirmed that Dg expression is sufficient to suppress the polarity defects associated with Dg 248 (Figure 3E).…”
Section: Resultsmentioning
confidence: 94%
“…One copy of the mRpL34 transgene rescues this phenotype completely (Figure 3D). This result was surprising since it has been reported that expression of a Dg transgene also rescues the Dg 248 polarity phenotype (Yatsenko et al., 2007). We therefore reproduced this experiment and confirmed that Dg expression is sufficient to suppress the polarity defects associated with Dg 248 (Figure 3E).…”
Section: Resultsmentioning
confidence: 94%
“…Although no other extracellular partners have been identified so far besides the C-terminal domain of α-DG, possible interactions of the β-DG ectodomain with other extracellular proteins cannot be ruled out. In line with this dynamic view of the DG complex is the observation that in Drosophila also the affinity between the cytodomain of β-DG and dystrophin peptides is in the micromolar range (Yatsenko et al, 2007).…”
Section: Maturation Of the Dg Precursor: The α/β Interface Puzzlementioning
confidence: 73%
“…A group of genes, including POSH , UbcD10 , and pie , came to our interest. POSH and UbcD10 , respectively, encode for Drosophila E3 and E2 ubiquitin ligase (Figure 2B) (Tsuda et al 2005; Yatsenko et al 2007); whereas pie , with predicted RING/PHD domains, shares highly conserved sequence with a human E3 ubiquitin ligase G2E3 (Shi et al 2003; Brooks et al 2008) The authors of a recent study have demonstrated that another ubiquitin-conjugating enzyme, Effete, maintains Drosophila GSCs through regulating cyclin A degradation (Chen et al 2009). The finding of this group of ubiquitin ligase genes to be essential for GSC maintenance suggests a potentially conserved role of ubiquitin-mediated proteolysis in stem cell self-renewal and tissue homeostasis.…”
Section: Resultsmentioning
confidence: 99%